Understanding the role of hepatic Neuronal PAS Domain Protein 2 (NPAS2) in circadian rhythmicity and cognition - Chrisp, Ruby (2023)
Circadian rhythms are highly conserved, endogenous biological oscillations with a periodicity of approximately 24 hours. These cycles have significant impacts on the sleep wake cycle, metabolism, mood, and cognition. A defining characteristic of these rhythms is their ability to be entrained by external stimuli, such as light and temperature, known as zeitgebers. Such rhythms are generated by a hierarchy of biological clocks which are centrally controlled by the suprachiasmatic nucleus (SCN) within the anterior hypothalamus. The SCN orchestrates phase synchronisation of clocks in peripheral tissues to allow for rhythmic regulation of endogenous processes throughout the day. Further understanding of circadian rhythms is important, since disruption of the clock and modern day non-circadian light schedules have been associated with cancers, metabolic diseases, and ageing. One gene central to the rhythmic control of physiological processes is neuronal PAS domain protein 2 (NPAS2). NPAS2 is a bHLH-PAS domain containing protein which is the lesser-known paralog of CLOCK. Both CLOCK and NPAS2 are transcription factors that can form heterodimeric complexes with BMAL1 in the positive limb of the core circadian transcription-translation feedback loop to initiate the transcription of clock-controlled genes. The presence of one of the two, NPAS2 or CLOCK, is vital to maintain rhythmicity, but in the absence of one, the other will compensate in circadian functionality. In addition to circadian roles, NPAS2 has been implicated in cognition and emotional long-term memory. Knockdown of NPAS2 has also been seen to cause anxiolytic effects in behavioural paradigms, and striatal NPAS2 levels increase following acute and chronic stress, showing an additional role for the circadian gene in stress responses. Here, we utilised conditional peripheral knockouts of NPAS2 in mouse models to elucidate the role of hepatic NPAS2 in global circadian rhythmicity, locomotor activity, recognition memory and anxiety. These experiments were originally performed as a peripheral control for brain specific knockout mice. To investigate peripheral NPAS2 roles in circadian period, phase and locomotor activity, pre- and post-natal hepatic NPAS2 knockout mice were employed in cycling and constant lighting conditions. These mouse models displayed no effect of loss of liver NPAS2 on entrainment or adaptation to constant lighting conditions, however, significant female-specific weight loss following social isolation was observed that was absent in C57BL/6J wild type controls. Most notably, significant sexual dimorphism in circadian parameters following extended time in constant light were revealed in control mice, indicating female superiority in light condition adaptation. This effect was lost in hepatic NPAS2 deleted models. Furthermore, novel object recognition tests uncovered significant differences in cognitive performance in constant light, in favour of post-natal hepatic NPAS2 knockout mice. Recognition tests also showed male superiority in the cognitive performance of control mice that was abolished in liver deleted NPAS2 mice. These results suggest a sex-specific mechanism by which hepatic NPAS2 may influence recognition memory. A proposed method by which cognition is altered following hepatic NPAS2 loss is through aberrant circadian gene expression within the brain. Downstream investigations into circadian gene expression in the frontal lobe revealed altered expression and phase of core clock genes Bmal1, Clock and Rev-erbß in animals with hepatic NPAS2 loss. Additionally, loss of sexually dimorphic central circadian gene expression was also noted in post-natal NPAS2 liver knockouts. Taken together, these results suggest, first, that hepatic loss of NPAS2 may influence centrally mediated behaviours such as cognition, and second, suggest this may represent a sex-specific mechanism. To complement the findings of this work, brain specific NPAS2 knockout mice could be employed to investigate the impact of direct NPAS2 loss in the brain on cognition and circadian gene expression.